The Role of Culture in National Authority from Imam Ali`s (A.S) Perspective - Mohammad Bagher Babaei Talatapeh (Taḥqīqāt-i Farhangī-i Īrān)
This article aims to study culture in relation to elements of national power and answer to this question that how Imam Ali sees situation of culture in relation with political, economic, social and military factors of national power. Based on content analysis method of sermons (khotba), poems and short words of Imam Ali, the findings reveal that he was more focused on culture during his statesmanship and gave more developmental, theoretical and valuable principles preference to other elements of power and national authority; in a way that Imam Ali`s political, social, economic and military behaviors, were more based on realism, truth-boundnes, god-centrality, perfectionism and human –revolveness,